Gambaran Klinis dan Pemilihan Tatalaksana Medikamentosa serta Operatif pada Kasus Tonsilitis Anak di Rumah Sakit Mardi Waluyo Metro Tahun 2023 - Vatiana Satyani (CV. Creative Tugu Pena, 2024)
Tonsillitis is a common disease among children caused by infection. Symptoms of tonsillitis such as sore throat and may also result in Obstructive Sleep Apnea (OSA). The World Health Organization (WHO) estimates that 287,000 children under the age of 15 undergo tonsillectomy with or without adenoidectomy. This study is a descriptive study with data collected from patient medical records for the year 2023 in September 2024 at Mardi Waluyo Hospital. This study included 147 samples, consisting of 78 males (53%) and 69 females (47%). Patients aged 0-5 years accounted for 26 cases (18%), those aged 6-10 years for 63 cases (43%), those aged 11-15 years for 42 cases (28%), and those aged 16-18 years for 16 cases (11%). Tonsil size measurements showed T2-T2 in 21 patients (14%), T3-T3 in 30 patients (21%), and T4-T4 in 96 patients (65%). Clinical symptoms included fever in 45 patients (31%), sore throat in 119 patients (81%), snoring in 94 patients (64%), and cough and cold in 80 patients (54%). Acute tonsillitis cases totaled 13 (9%), while chronic cases numbered 134 (91%). Treatment consisted of medication for 59 patients (40%) and surgery for 88 patients (60%). The most common cases of tonsillitis at Mardi Waluyo Hospital in 2023 were chronic tonsillitis among children aged 6-10 years, with the most frequent symptom being sore throat. The most prevalent tonsil size was T4-T4, which predominantly received surgical treatment, with a male majority